2014
DOI: 10.1115/1.4028209
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Enriched Combustion Testing of Siemens Industrial SGT-400 at Atmospheric Conditions

Abstract: In order to further extend the turbine fuel flex capability, a test under atmospheric condi tions of a full-scale SGT-400 burner was performed to study the combustion behavior when operating on hydrogen enriched natural gas (NG). A high speed camera was in stalled in the rig to investigate the flame dynamics on different operation conditions. NOx emissions were measured for all presented conditions. The combustion system was instru mented with thermocouples on all the key locations to allow flame position moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…At the same full load firing temperature, the RMS pressure fluctuations were reported to be three times higher compared to 100% natural gas operation. Prior high speed imaging at atmospheric pressure using the same combustor [88] showed a more compact H 2 flame compared to the methane flame with more intense burning and unsteady heat release characteristics. This indicates that hydrogen addition not only rendered the combustor unstable, the effect was exacerbated with increasing pressure.…”
Section: Elevated Pressurementioning
confidence: 92%
See 1 more Smart Citation
“…At the same full load firing temperature, the RMS pressure fluctuations were reported to be three times higher compared to 100% natural gas operation. Prior high speed imaging at atmospheric pressure using the same combustor [88] showed a more compact H 2 flame compared to the methane flame with more intense burning and unsteady heat release characteristics. This indicates that hydrogen addition not only rendered the combustor unstable, the effect was exacerbated with increasing pressure.…”
Section: Elevated Pressurementioning
confidence: 92%
“…Using Large Eddy Simulation (LES), Moëll et al [73] simulated the effect of hydrogen enrichment on combustion instabilities in the third generation DLE burner used by Siemens Energy in the SGT-800 industrial gas turbine. The computational model was based on an experimental test rig which has been used for various studies [72,76,88]. The study [73] compared the flame dynamics of 100% CH 4 with a blend of 70% CH 4 and 30% H 2 by volume at the same adiabatic flame temperature.…”
Section: Elevated Pressurementioning
confidence: 99%
“…Compared to natural gas, the technological problems associated with hydrogen include a higher flame speed, a higher adiabatic flame temperature, shorter delay times, a wider range of flammability, and an increase in the volumetric fuel flow rate [30] [31]. A test on a SGT-400 industrial gas turbine burner to study hydrogen-enriched combustion at atmospheric conditions shows that hydrogen volumetric composition of up to 30% could still maintain stable operation [32] and testing on the high pressure condition shows that up to 20% H2 volumetric composition the combustion system can operate up to 20% of the H2 volumetric composition without the risk of flashback [33].…”
Section: Technology Reviewmentioning
confidence: 99%
“…An experimental investigation hydrogen rich fuel on gas turbine was performed by Lam et.al. (Lam et al , 2015). No flames were detected in the investigation and from the results they concluded that to achieve improvement in the combustion efficiency the design of ignition system needs to be concentrated by injecting hydrogen at higher proportions.…”
Section: Combustion Characteristicsmentioning
confidence: 99%